Analisis Indeks Pembangunan Manusia: Investasi Pendidikan sebagai Peningkatan Daya Saing Bangsa - Perkasa, Ripho Delzy (Jurusan PIPS FKIP UMMY Solok, 2017)
Writing this article aims to illustrate: 1). Description of Human Development Index of Indonesia. 2) The steps taken by the Indonesian government on education in improving the nation's competitiveness. This article uses literature study approach. Education is one component in the measurement of human development index. So basically the high level of human development index should describe the ideal condition, but in fact the increasing index of human development in Indonesia does not necessarily mean that with a good level of education will give birth to a prosperous individual or society but there is still considerable inequality from various layers community.